azam DESIGNING A SYLLABUS AND MATERIALS TO ENCOURAGE EFFECTIVE COMMUNICATION IN CLASS AND AVOIDING TRADITIONAL SYLLABUSES: DESIGNING A SYLLABUS AND MATERIALS TO ENCOURAGE EFFECTIVE COMMUNICATION IN CLASS AND AVOIDING TRADITIONAL SYLLABUSES - Ernazarov, Azam (Журнал иностранных языков и лингвистики, 2022)
In recent days, English language is taught in variety of manners and contexts, namely it is taught by various methods and syllabuses according to the learners’ needs, levels and background country. For example, in EFL setting, the syllabus that teachers follow in the classroom varies in different ways.